Propranolol (1 mg/kg/day) with intralesional bleomycin versus propranolol monotherapy for infantile hemangioma: a randomized controlled trial - Guo, Yanyan; Liu, Xinxian; He, Sicheng; Zhou, Bin (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy and safety of oral propranolol (1 mg/kg/day) combined with intralesional bleomycin injections versus propranolol monotherapy at the same dosage for infantile hemangioma (IH). This study investigates if a low-dose propranolol regimen can be enhanced with local therapy to improve outcomes while maintaining a favorable safety profile.MethodsThis single-center, prospective, randomized controlled trial enrolled 260 infants (aged 3–11 months, mean age 5.34 ± 2.57 months) with IH requiring systemic therapy. Participants were randomly assigned (1:1) to either the combination group (propranolol plus monthly intralesional bleomycin, n = 130) or the monotherapy group (propranolol alone, n = 130). The primary efficacy endpoint was the proportion of patients achieving an excellent therapeutic response (complete regression or marked effectiveness) at 6 months. Secondary outcomes included early therapeutic response, changes in hemangioma color score, tumor volume reduction, Vancouver Scar Scale (VSS) scores, and incidence of adverse events.ResultsBaseline characteristics were comparable. After 6 months, a significantly higher proportion of patients in the combination group achieved the primary endpoint (77.69% vs. 50.00%; P < 0.001). The combination group had higher rates of complete regression (33.07% vs. 15.38%, P = 0.001) and marked effectiveness (44.61% vs. 34.61%, P = 0.083). A superior early response was noted in the combination group, with a more pronounced degree of tumor atrophy within 24 h (P < 0.001). Post-treatment color scores (change from baseline, P < 0.001) and tumor volume (1.63 ± 0.70 cm3 vs. 3.27 ± 1.06 cm3, P < 0.001) were significantly better in the combination group. VSS scores were significantly lower in the combination group (3.68 ± 0.37 vs. 5.75 ± 0.64; P < 0.001), indicating less scarring. Safety profiles were comparable.ConclusionIn infants with IH, augmenting a low-dose oral propranolol regimen (1 mg/kg/day) with monthly intralesional bleomycin is significantly more effective than low-dose propranolol monotherapy. This combination strategy accelerates tumor regression and yields superior cosmetic outcomes, all while maintaining a comparable safety profile.